Power structure among female inmates at Iloilo City District Jail-Female dorm (Bureau of Jail Management and Penology). - Tranco, Sharon Mae Q.
This is a qualitative study of the dynamics of power structure among female inmates at Iloilo City District Jail-Female Dorm (Bureau of Jail Management and Penology). This study was conducted at Iloilo City District Jail- Female Dorm at General Luna Street, City Proper, Iloilo City using structured and unstructured interviews with inmates, observations inside the jail, key informant interviews among jail officers/personnel and documents from the Operations Division of the Bureau of Jail Management and Penology Regional Office VI. The following are the results of the study: (1) Groupings among inmates are determined by gender (homosexuals) and type of case (RA9165 and Non-RA9165) and characterized by less violent interaction among them, (2) Prevalence of drug cases with female inmates in Iloilo City District Jail which constitutes three-fourths of the jail population, (3) Formal and Informal Hierarchy inside the jail exists within groups and those set by the jail management, (4) Presence of Structural Variables that affect hierarchical power structure among inmates: Occupation, Religion, Education, Type of Case Committed, Length of Stay in jail and inmate?s personality were the identified structural variables inside the Iloilo City District Jail-Female Dorm, (5) Presence of homosexual relationships in jail which is common and distinct since it has a unique dynamics in female jail facilities, (6) Contrary to what the authors in the literature views hierarchal structure among female inmates, it was found out that hierarchy at Iloilo City District Jail-Female Dorm is dominated by the RA 9165 at the top of the hierarchy and they are the sources of the informal authority inside the jail. Iloilo City District Jail-Female Dorm is an example of community, wherein inmates, even though considered being the most deprived groups in the society still struggle to compete with each other in the jail community?s hierarchical structure.